The Concept and Implementation of Customary Law in Indonesian Society - Handayani, Yuli (Rechtsvinding, 2025)
Customary law is a legal system that has grown and developed within Indonesian society, rooted in cultural values, traditions, and local customs. This law is living, dynamic, and possesses normative authority recognized within the national legal system. This article aims to elaborate on the fundamental concepts of customary law, its characteristics, and its application within the context of modern Indonesian society. The study employs a qualitative descriptive approach through a literature review method, drawing on various legal sources and previous research. The findings indicate that customary law not only functions as a regulator of social behavior but also serves as a moral foundation for maintaining societal harmony. Despite the challenges posed by globalization and modernization, customary law remains relevant as long as it can adapt to the principles of social justice and the national legal framework.